Identifikasi Penerimaan Pinjaman Modal Usaha dengan Metode Backward Chaining - Miftahul Mardiyah; Jufriadif Na’am; Gunadi Widi Nurcahyo (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2025)
Cooperatives are financial institutions in conducting savings and borrowing transactions. This study aims to identify borrowers accurately so that the distribution of funds is right on target. The method used is Backward Chaining. The results of this study are the level of accuracy in identifying loan recipients to be high, namely loan funds can be disbursed within one day. So this study can be used as a recommendation in identifying borrowers in all cooperatives.